Amygdala GABA Neurons Project To vlPAG And mPFC. (June 2019) - Sun, Ying; Blanco-Centurion, Carlos; Zou, Bingyu; Bendell, Emmaline; Shiromani, Priyattam J.; Liu, Meng
Highlights: Single amygdala GABA neuron projects to both brain stem and cortex. Bifurcating amygdala neurons may regulate emotions and muscle tone. Abstract: The amygdala regulates multiple behaviors and emotions by projecting to multiple brain regions. However, the topographical distribution of amygdala neurons projecting to specific brain areas is still unclear. In the present study, we focus on determining whether single amygdala neurons project to the brain stem ventrolateral periaqueductal grey (vlPAG) and to the medial prefrontal cortex (mPFC). The mPFC neurons are involved in detecting emotional content while the vlPAG neurons are involved in regulating muscle tone. In VGAT-Cre mice a cre-inducible retrograde AAV tracer expressing tdTomato was microinjected into the ventrolateral periaqueductal grey matter (vlPAG), while a second retrograde AAV tracer with generic expression of GFP was delivered into the medial prefrontal cortex (mPFC). The results identified a subgroup of bifurcating GABAergic neurons in the central nucleus (CeA) and basolateral amygdala (BLA) that projects to vlPAG and mPFC. Based on these projections we suggest that amygdala GABA neurons may be involved in triggering emotionally-induced cataplexy in the sleep disorder, narcolepsy.